Human brain trauma severity is associated with lectin complement pathway activation. Issue 5 (May 2019) - De Blasio, Daiana; Fumagalli, Stefano; Orsini, Franca; Neglia, Laura; Perego, Carlo; Ortolano, Fabrizio; Zanier, Elisa R; Picetti, Edoardo; Locatelli, Marco; Stocchetti, Nino; Longhi, Luca; Garred, Peter; et al.
We explored the involvement of the lectin pathway of complement in post-traumatic brain injury (TBI) pathophysiology in humans. Brain samples were obtained from 28 patients who had undergone therapeutic contusion removal, within 12 h (early) or from >12 h until five days (late) from injury, and from five non-TBI patients. Imaging analysis indicated that lectin pathway initiator molecules (MBL, ficolin-1, ficolin-2 and ficolin-3), the key enzymes MASP-2 and MASP-3, and the downstream complement components (C3 fragments and TCC) were present inside and outside brain vessels in all contusions. Only ficolin-1 was found in the parenchyma of non-TBI tissues. Immunoassays in brain homogenates showed that MBL, ficolin-2 and ficolin-3 increased in TBI compared to non-TBI (2.0, 2.2 and 6.0-times) samples. MASP-2 increased with subarachnoid hemorrhage and abnormal pupil reactivity, two indicators of structural and functional damage. C3 fragments and TCC increased, respectively, by 3.5 - and 4.0-fold in TBI compared to non-TBI tissue and significantly correlated with MBL, ficolin-2, ficolin-3, MASP-2 and MASP-3 levels in the homogenates. In conclusion, we show for the first time the direct presence of lectin pathway components in human cerebral contusions and their association with injury severity, suggesting a central role for the lectin pathway in the post-traumatic pathophysiology of human TBI.